Photoelastic evaluation of the effect of composite formulation on polymerization shrinkage stress - Karla Mychellyne Costa Oliveira; Simonides Consani; Luciano Souza Gonçalves; William Cunha Brandt; Renzo Alberto Ccahuana-Vásquez (Sociedade Brasileira de Pesquisa Odontológica, 2012)
We compared polymerization stress in two commercial composites and three experimental composites made using camphorquinone (CQ) and/or phenylpropanedione (PPD) as photoinitiators. The internal surfaces of photoelastic resin discs with cylindrical cavities were roughened and treated with adhesive. Composites were divided into five groups: two commercial composites (Filtek Silorane and Filtek Z250) and three experimental composites with CQ/amine, CQ/PPD/amine, and PPD/amine. Composites were photopolymerized inside cavities, and subjected to photoelastic analysis immediately and at 24 hours and 7 days later using a plane polariscope. Stress created by Silorane (3.08 ± 0.09 MPa) was similar to that of Z250 (3.19 ± 0.13 MPa) immediately after photopolymerization (p > 0.05). After 24 hours and 7 days, Z250 (3.53 ± 0.15 and 3.69 ± 0.10 MPa, respectively) showed higher stress than Silorane (3.19 ± 0.10 and 3.16 ± 0.10 MPa, respectively). Qualitative analysis immediately after photopolymerization showed composite/CQ promoted higher stress than PPD, but stress levels at other evaluated times were statistically similar, varying between 3.45 ± 0.11 MPa and 3.92 ± 0.13 MPa. At 24 hours and 7 days, Silorane created the lowest stress. All photoinitiators created comparable tensions during polymerization.